Purification of molybdenum, growth and characterization of medium volume ZnMoO4crystals for the LUMINEU program - Bergé, L.; Enss, Christian; Fleischmann, Andreas; Gastaldo, Loredana (Journal of Instrumentation, 2014)
The LUMINEU program aims at performing a pilot experiment on neutrinoless double beta decay of 100Mo using radiopure ZnMoO4 crystals operated as cryogenic scintillating bolometers. Growth of high quality radiopure crystals is a complex task, since there are no commercial molybdenum compounds available with the required level of purity and radioactive contamination. This paper discusses approaches to purify molybdenum and synthesize compounds for high quality radiopure ZnMoO4 crystal growth. A combination of a double sublimation (with addition of zinc molybdate) with subsequent recrystallization in aqueous solutions (using zinc molybdate as a collector) was used. Zinc molybdate crystals up to 1.5 kg were grown by the low-thermal-gradient Czochralski technique; their optical, luminescent, diamagnetic, thermal and bolometric properties were tested.